Functional Organization of the Sympathetic Pathways Controlling the Pupil: Light-Inhibited and Light-Stimulated Pathways - Szabadi, Elemer (Frontiers in Neurology, 2018)
Pupil diameter reflects the balance between opposing sympathetic and parasympathetic outputs to the iris. Pupil dilation is mediated by a sympathetic output acting in opposition to parasympathetically mediated pupil constriction. While light stimulates the parasympathetic output, giving rise to the light reflex, it has a dual effect on the sympathetic output: it can both inhibit and stimulate it. Light-inhibited and light-stimulated sympathetic pathways (LISPs and LSSPs) mediate the opposite effects of light on sympathetic activity. Two LISPs and two LSSPs are described. The pretectum/PAG pathway runs from the pretectum, via the periaqueductal grey (PAG), to sympathetic premotor neurones (SympPN) in the paraventricular nucleus (PVN) of the hypothalamus, rostral ventrolateral medulla (RVLM), locus coeruleus (LC), and dorsal raphe nucleus (DRN). Some of these SympPN project to preganglionic sympathetic neurones that innervate the iris via the superior cervical ganglion (SCG) projecting to the iris. The SCN/PVN pathway overlaps with that controlling melatonin synthesis: it runs from the suprachiasmatic nucleus (SCN) to the PVN that projects to pupil-controlling sympathetic preganglionic neurones in the spinal cord. The LISPs, by attenuating sympathetic activity, allow unimpeded operation for the light reflex. The two LSSPs are the noradrenergic and serotonergic pathways. The noradrenergic LSSP runs from the SCN, via the dorsomedial hypothalamus (DMH) to the LC that contains both SympPN and parasympathetic preganglionic neurones (ParaPN). The SympPN project to sympathetic preganglionic neurones in the spinal cord where they stimulate excitatory α1-adrenoceptors, whereas the ParaPN project to parasympathetic preganglionic neurones in the Edinger-Westphal nucleus of the light reflex pathway, where they stimulate inhibitory α2-adrenoceptors. The hub of the serotonergic LSSP is the DRN that is light-sensitive, both directly and indirectly (via an orexinergic input). The LSSPs mediate a latent mydriatic effect of light on the pupil that can be unmasked by drugs that either inhibit or stimulate SympPN in these pathways. By attenuating light-evoked pupil constriction, LSSPs may allow diurnal animals to funtion during daytime. The noradrenergic LSSP has widespread connections to neural networks controlling a variety of functions, such as sleep/arousal, pain and fear/anxiety. Many physiological and psychological variables modulate pupil function via this pathway.